Soups, salads, sandwiches - Matheson, Matty (Ten Speed Press, 2024)
Packed with character, personal stories, 126 recipes and photographs of a day-in-the-life with Matty and his family, a cookbook that will revolutionize how you think of these kitchen basics--soups, salads and sandwiches--is full of the author's signature twists on the classics delivered with minimal effort for maximum flavor.